Peta Sebaran Salinitas Pada Sumur Bor di Desa Percut Kecamatan Percut Sei Tuan Kabupaten Deli serdang - Deliana Dongoran; Yunus Afifuddin; Riri Ezraneti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The rapid development of technology, followed by the development of the residents,this resulted in the siphoning of water by society include on wellbore massively which resulted in the decrease of fresh water surface elevation with the result that be lower than the sea level. The purpose of this reseach was to analyze salinity value and typesof waterat each sample pointon Wellbore, thesalinity distribution maps, influence of the depth to well salinity, and looking for away of managing water resources in Percut village, Sub-district of Percut Sei Tuan District of Deli Serdang. This reseach used Arcgis 9,3 software to got salinity distribution map. The result showed that well sanility in every stasiun was different. Salinity average was 333 – 2333 mg/l and in category of fresh water was 8,5%, brackish water was 23,6% and middle 67,9%. At depths of 20 – 100 meters, water were included in very good category not found was discovered at a depth of>100 meters. It showed that water in percut village was not suitable as drinking water.Keywords : Map, Salinity, wellbore.